Utilization Of Human Resources Analytics In Corporate Strategic Decision Making at PT Coca Cola Amatil Indonesia - Laura Mizela da Costa; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
This study examines the use of Human Resource (HR) Analytics in strategic decision-making in companies, with a case study at PT Coca Cola Amatil Indonesia. The approach used is qualitative, using library research methods and in-depth interviews with managers and staff of the company's HR department. HR Analytics is a data-based approach used to analyze trends, performance, and predictions of human resources to support more accurate strategic decisions. The study results indicate that PT Coca Cola Amatil Indonesia has implemented HR Analytics in several critical aspects, such as recruitment, performance management, and employee retention. The data collected is used to identify potential risks, support workforce planning, and improve organizational efficiency and productivity. These findings indicate that the use of HR Analytics has a significant contribution to strategic decision-making and increasing the company's competitiveness sustainably.